Avoiding Plagiarism in Writing a Research Paper - Majid Wajdi; I Made Sumartana; Ni Putu Dyah Hudiananingsih (Soshum: Jurnal Sosial dan Humaniora, 2018)
This paper discusses how to avoid plagiarism in a research paper. Avoiding plagiarism is part of a scientific writing ethic that always stated in any publication. Every writer should pay attention to their papers submitted to a journal or a scientific forum that they are free from unethical conduct. Writing a research paper needs overall accuracy especially in avoiding plagiarism in the paper that is to be published in a journal or to be presented at a certain scientific meeting, seminar or symposium. It is based on writers’ experience as a paper writer as well as a journal reviewer. The first application that the writers use is ‘checker’, a Mac computer application, used to check spelling and grammar. It assists the writers to check how misspelling and an ungrammatical inaccuracy in the writers’ papers. The second free application is ‘plagiarism checker’. Checking originality of a paper is essential and it is not too difficult to do today. It is freely accessible that plagiarism checker can be used to check how original the paper is. By visiting “Google” then write down ‘plagiarism checker’, it will appear ‘smallseatools’ and then the writers could choose and check how original the paper is. This application is freely accessed and helps immensely to check how original a paper is and how far a paper is free from plagiarism. The unoriginal phrase will be underlined and marked red and finally will be shown how inimitable the paper is. Plagiarism scan report which consists of the date of the report, plagiarism status, total words and total characters can be downloaded.